Aplikasi Penggajian Karyawan dengan Laravel di Dinas Pertanian, Pangan, Kelautan, Perikanan Provinsi Papua Tengah - Lusia Esterina Konsita; Kristia Yuliawan (STMIK Pesat Nabire, 2025)
An effective and accurate employee payroll application is crucial to support the operations of the Department of Agriculture, Food, Marine, and Fisheries of Central Papua Province. This study aims to develop a payroll application system using the Laravel framework that can assist in the payroll management process more efficiently and structurally. The methodology used includes needs analysis, system design, implementation, and testing. The results show that this application can improve efficiency and accuracy in employee payroll management in the relevant department. The implementation of this application is also expected to reduce manual errors and enhance transparency in the payroll process.